Lembaga Keuangan Mikro dan Manajemen Risiko Kredit: Sebuah Perspektif dari Perempuan Usaha Mikro - Koesworo, Yulius; Ardhanari, Margaretha; Sina, Siprianus S. (Kajian Manajemen dan Bisnis, 2009)
This paper develops framework of women micro entrepreneurs empower in order to analyze the contribution of 60% from 41 million of them in economic growth. The aims of this research are (1) analyze the impact of micro credit services towards business development among women micro entrepreneurers, (2) observes the relationships between micro finance institution and women micro entrepreneurs performance, (3) analyze the degree of credit risk faced by women micro entrepreneurs.